2002
DOI: 10.1002/1521-4141(200205)32:5<1338::aid-immu1338>3.0.co;2-4
|View full text |Cite
|
Sign up to set email alerts
|

Cross-sensitization to haptens: formation of common haptenic metabolites, T cell recognition of cryptic peptides, and true T cell cross-reactivity

Abstract: To analyze T cell cross‐reactivity to para‐compounds, we established CD4+ T cell hybridomas from mice immunized with adducts of self‐globin and one of three different para‐compounds: p‐aminophenol, p‐phenylenediamine, or Bandrowski's base. Some of the hybridomas obtained reacted not only to the immunizing antigen, but also to metabolically related para‐compounds, bound to the same protein, thus suggesting formation of common metabolites. Other hybridomas cross‐reacted to globin adducts of metabolically unrelat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 26 publications
1
14
0
1
Order By: Relevance
“…69). It is noteworthy to point out that reductive metabolism of the nitro group to the corresponding reactive nitroso metabolite has also been proposed as an alternate mechanism of bioactivation leading to toxicity [47]. Chloramphenicol has been reported to be a suicide substrate for cytochrome P450 [464]; its mechanism of inactivation may be similar to that hypothesized below.…”
Section: Mechanismmentioning
confidence: 99%
See 1 more Smart Citation
“…69). It is noteworthy to point out that reductive metabolism of the nitro group to the corresponding reactive nitroso metabolite has also been proposed as an alternate mechanism of bioactivation leading to toxicity [47]. Chloramphenicol has been reported to be a suicide substrate for cytochrome P450 [464]; its mechanism of inactivation may be similar to that hypothesized below.…”
Section: Mechanismmentioning
confidence: 99%
“…Following several challenges with the immunogen, the antiserum is screened for the antibody titer using an enzyme-linked immunosorbent assay (ELISA). The antibody then can be used to identify haptenized protein via Western blot analysis [47][48][49]. While this method can be a very powerful technique for the identification and characterization of cellular constituents that have undergone covalent modification by a reactive metabolite, it is generally a low-throughput and a time consuming method for the detection of reactive intermediates; and finally, (5) metabolite identification: An understanding of metabolic pathways and the biochemical mechanisms by which metabolites are synthesized can give insight to the potential of a compound to yield a reactive species [39].…”
Section: Experimental Strategiesmentioning
confidence: 99%
“…Wulferink et al [27] observed murine T-cell responses to globin adducts of metabolically unrelated compounds. Metabolite-protein complexes were recognized by T cells as cryptic self-peptides, even though the metabolites themselves were completely dissimilar.…”
Section: Cellular Response To Parent Drug and Metabolitesmentioning
confidence: 99%
“…It is a long-standing hypothesis that sensitization can only occur if the sensitizing chemical (or hapten) binds to a skin protein (Landsteiner and Jacobs, 1936; Dupuis and Benerzra, 1982). However, some investigators in the field would refute the hypothesis that covalent binding is a prerequisite for sensitization in favor of noncovalent modes of protein-hapten association (7) or the modification of normal self-protein processing resulting in the generation of cryptic epitopes (8). It is therefore vital for the future development of in silico and in vitro methodologies that we understand fully the links between protein -hapten binding and ability to cause sensitization.…”
Section: Introductionmentioning
confidence: 99%